Can human amniotic membrane be used as an Ideal Suture or Filling Material? An Experimental study - Fatma Bilgen; Alper Ural; M Nuri Karatoprak; Mehmet Bekerecioğlu (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2019)
Background: The use of the patient's own tissues in surgery increases the morbidity rate, whereas the use of injected or implanted materials can cause allergic reactions in the body mostly via immunogenic pathways. In addition, absorbable suture materials and some fillers used in almost all surgical applications can cause reactions in the body.  Objective: The use of human amniotic membrane (HAM) as a suture and/or filling material has been successfully investigated in many areas to solve or minimize these problems.  Material and Method: In this study, 40 rats were divided into four groups (10 rats per group). The HAM was removed with the surrounding tissue at the first week from group 1, the second week from group 2, the first month from group 3, and the third month from group 4, and underwent clinical and histopathological examination.  Results: When the rats that had HAM placed under the skin and intramuscle were evaluated statistically using a points-based scoring system, there was a statistically significant difference among all groups (p<0.001).  Conclusion: In our study, we found that HAM progressively biodegraded by macrophages within 3 months could be used as an absorbable suture material; therefore, its use as a filling material was limited over time. In addition, it is also likely to be used as an absorbable suture material, as it can accelerate wound healing due to the growth factors secreted. However, further studies are needed to prevent adhesions of factors isolated from amniotic fluid or the HAM and to investigate its use in wound healing.